Sequence Pair-Based Scatter Search Approach for Cell Formation and Layout Considering Unequal Machine Dimensions and Cell Input and Output Locations - 郑永前 钱伟俊 (东华大学学报（英文版）, 2015)
In the purpose of dealing with the inconsistency of the machine dimensions in cell formation and layout problems,comprehensively taking into account such factors as alternative process routings, lot splitting, cell input and output（ I / O）locations,an integrated cell formation and layout model considering unequal machine dimensions is established which aims at minimizing intra-cell material handling cost,inter-cell material handling cost and cell expansion cost. A sequence pair-based scatter search algorithm is proposed which simultaneously adopts the roulette wheel selection operator as a subsets combination method to improve the quality of new solutions and the dynamic reference sets updating method to accelerate the convergence rate. Through the comparison of the results achieved by the proposed algorithm, Lingo and simulated annealing under different problem scales,the correctness of the model and the effectiveness of the algorithm are verified.